An inertial neuro-dynamic system for solving zero-one integer programming - Wei, Shuting; He, Xing (2021 International Conference on Neuromorphic Computing (ICNC), 2021)
This paper presents an inertial neuro-dynamic system to solve zero-one integer programming. We transform the problem of zero-one integer programming into a relatively easy problem only subject to linear equality constraints by using a nonlinear complementarity problem function. Subsequently, a inertial neuro-dynamic system is proposed to solve above transformed problem. It is shown that the proposed inertial neuro-dynamic system is stable and the equilibrium point converges to optimal solution set. It is worth emphasizing that our developed inertial neuro-dynamic system achieves faster convergence speed and explores more optimal solutions in a fixed initial value by adjusting the inertial factor. Finally, according to the experimental results on two illustrative examples, the proposed method is highly effective.